2016
DOI: 10.7763/ijssh.2016.v6.611
|View full text |Cite
|
Sign up to set email alerts
|

How SNS Mediates EFL Adolescent Learners in Language Learning – From Learners' Perspectives

Abstract: Abstract-Abundant studies have shown that incorporating SNSs (social networking site) brings positive effects on language teaching and learning and enhances learners' learning spirit, interactions as a whole.However, a large body of the research focused mainly on tertiary education. Adolescents' perspectives are often neglected. To fill the interstice, this mix-method research was conducted in 2012 to examine how a group on a SNS assists 9 EFL adolescent learners' English learning. The two research questions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The participants were interested in interest-based topics such as entertainment, grammar and the university. Chen (2016) advocates that since many instructors use Facebook language learning is their classes, the lack of effective pedagogies of teaching English language on Facebook is worrying to ensure the efficacy of learning English on Facebook.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The participants were interested in interest-based topics such as entertainment, grammar and the university. Chen (2016) advocates that since many instructors use Facebook language learning is their classes, the lack of effective pedagogies of teaching English language on Facebook is worrying to ensure the efficacy of learning English on Facebook.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nevertheless, there are some studies indicated that students felt reluctant to engage Facebook-based activities because uploaded contents were unhelpful and irrelevant to the topics they concerned (Kasuma & Wray, 2015) [104] or Chen (2016) [105] discussed that there were not effective methodologies were delivered to all students on the Facebook group by English teachers.…”
Section: Social Networking Sites (Snss) In Eltmentioning
confidence: 99%